A Software Tool for the Design and Operational Analysis of Pressure Vessels used in Offshore Hydro-pneumatic Energy Storage. (August 2021) - Cutajar, Charise; Sant, Tonio; Farrugia, Robert N.; Buhagiar, Daniel
Highlights: Optimisation algorithm finds the minimum material requirements for offshore an HPES system PVs with a nominal diameter-to-thickness ratio smaller than 30 can self-anchor Optimal conditions are obtained at pressure ratios between 2.4 and 2.6 Changes in sea depth or peak pressure may shift the value of optimal pressure ratio Abstract: Despite the breakthroughs and rapid growth in the global installed offshore wind capacity over the last two decades, a prevailing major challenge is the intermittent nature of the wind resource itself. Consequently, co-locating energy storage systems with wind turbines deployed out at sea is perceived as a key component that will help to overcome this crucial challenge and address the mismatch between the supply of green energy and actual energy demand in real time. Of particular interest are hydro-pneumatic energy storage solutions that can deliver a safer and more reliable operation for a longer life span when compared to electro-chemical storage solutions. This paper presents a smart software tool named SmartPVB, which has been specifically developed for the optimisation of the design of pressure vessel bundles used in offshore hydro-pneumatic energy storage systems. The optimised design parameters obtained through the software SmartPVB help drive the material requirements to a minimum. A sensitivity study to analyse the influence of various parameters on a hydro-pneumatic energy storage system mounted on the seabed at a water depth of 200 m is also outlined. Results suggest that the optimal operating pressure ratio to minimise steel requirments for the pressure vessel bundle lies between 2.4 and 2.6. Furthermore, it is shown that the overall mass of the pressure vessel bundle per unit of storage capacity increases with sea depth, while it decreases with increasing peak operating pressures up to 200 bar.